COVID-19 Fear and Anxiety in Patients with Diabetes Mellitus and their Effect on HbA1c - Tura Bahadır, Çiğdem; Özçetinkaya Erdoğan, Serap (Acta Medica, 2022)
Objective: To determine the severity of fear and anxiety of COVID-19 in diabetic patients and to evaluate their relationship with HbA1c. Materials and methods: Between December 2020 and March 2021, a total of 249 patients were included in the study. Demographic characteristics, duration of diabetes, glycosylated hemoglobin A1c (HbA1c) values of the patients were recorded. Fear and anxiety related to COVID-19 were evaluated with the validated Turkish version of the Fear of COVID Scale (FCS) and Coronavirus Anxiety Scale (CAS). FCS and CAS were compared between the diabetic group and the control group. The relationship between FCS and CAS and HbA1c, diabetes year, age, gender, educational status, place of residence, and employment status was investigated. Results: Median level of HbA1c and duration of diabetes mellitus were 7.65% (range 5.4-13.6) and 10 years (range 1-32) respectively. FCS was higher in the diabetic group compared to the control group (p=0.025). There was no significant difference between the diabetic and control groups regarding CAS. There was no relationship between HbA1c and FCS and CAS (p=0.919, r=0.008, p=0.725, r=0.027, respectively). Anxiety was higher in females than males in diabetic groups (p=0.009). Conclusions: The fear of COVID-19 is higher in diabetic patients compared to the general population. There was no relationship between fear and anxiety of COVID-19 and HbA1c. However, to protect long-term mental health, there should be strategies to detect and reduce the anxiety and fear caused by the pandemic in the services for diabetic patients.